Bottom-up and top-down methods to improve catalytic reactivity for photocatalytic production of hydrogen peroxide using a Ru-complex and water oxidation catalysts1. Issue 23 (21st June 2015) - Isaka, Yusuke; Kato, Satoshi; Hong, Dachao; Suenobu, Tomoyoshi; Yamada, Yusuke; Fukuzumi, Shunichi
<x xml:space="preserve">Abstract</x> Hydrogen peroxide (H2O2) was produced from water and dioxygen using a Ru-complex photocatalyst and water oxidation catalysts of metal-containing nanoparticles produced in situ under visible light irradiation.